435 Palliative electrochemotherapy in vulvar cancer: a double institution study and review of the literature. (13th November 2020) - Corrado, G; Cutillo, G; Fragomeni, S; Bruno, V; Tagliaferri, L; Mancini, E; Certelli, C; Vizza, E; Scambia, G; Garganese, G
Abstract : Introduction: The aim of this study is to revise the experience of two reference centers for vulvar cancer treatment during the last 2 years, evaluating the ECT procedure in terms of clinical outcome and side effects profile. Methods: Data were retrospectively collected from November 2017 to November 2019 in two Italian oncologic Institutes: Regina Elena Institute and Fondazione Policlinico Universitario Agostino Gemelli. ECT was offered in a palliative setting to patients with a primary or recurrent vulvar cancer diagnosis unsuitable for surgery or any other treatment, because of poor performance status or previous delivered treatments. All patients underwent general anaesthesia. Intravenous Bleomycin was administered. Follow-up examinations were performed at 1, 3 and 6 months. Results: 15 patients were included in the study. No intra-procedure complications occurred. 1 patient had pneumonia during post-operative stay. 1-month overall response rate (2 CR and 10 PR) was 80%. At 3-month follow-up, 3 patients (20%) showed PD, 3 patients (20%) died from the ongoing disease, 1 patients (6.7%) died for other reasons, whereas the other patients maintained their 1-month clinical response. 8 out of 13 patients (61.5%) were alive at 6-month follow-up, whereas 6 out of 12 patients (50%) were alive at 1-year follow-up. Conclusion: ECT has proven to be a feasible, easy to perform, reproducible and repeatable procedure. For these reasons, it may have a role in the management of VC, especially as palliative treatment when other therapies are no longer applicable.